Latin American immigrants in global cities: Interdisciplinary approaches to the analysis of communication, media and cultural practices - Retis, Jessica (2018)
The study of communication, media and cultural practices in diasporic contexts gives rise to a series of theoretical and methodological challenges. The current article examines these challenges and argues how interdisciplinary approaches constitute an enriching assembly which enables us to analyze and understand the process of arrival and settlement of Latin American immigrants in global cities. The compared study of Latin American diasporas and the media in urban environments also enables the identification of present trends. Migration and media studies function as a starting point towards identifying the critical analysis of the transnational condition among Latin Americans who reside in cities outside their region. We analyze how the genesis and consolidation of transnational and translocal audiences have been recognized by both the advertising market and private industries. Despite this, public administrations from countries of origin and destination still neglect their study.